ÜLKEMİZ KOŞULLARINDA NÖRONAL İNTESTİNAL DİSPLAZİ TANISI KONABİLİR Mİ? - TOPUZLU TEKAND, Gonca; ERDOĞAN, Ergun; Dervişoğlu, Sergülen; SARIMURAT, Nüvit; YEKER, Daver; YEŞİLDAĞ, Ebru; MOBİN, Afaq Alhaq; ÜNAL, Temurçin (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Classic aganglionosis is detected in only 50% of patients presenting with clinical symptoms of Hirschsprung’s disease; neuronal intestinal dysplasia (NID) is the real pathology in 20-40% of this group. Herein, the outcome of cases presenting with complaints related to bowel dysmotility and diagnosed to have NID, is evaluated. Results.- 8 NID cases, admitted to our unit had gastrointestinal decompression, barium enema and anorectal manometry, performed routinely. The full thickness rectal biopsies, peroperative colonic biopsy and anal myectomy samples were histopathologically evaluated with hematoxylin eosin stain (HE). Those cases histopathologically labeled as NID were either given oral Cisapride or surgically treated and followed up. In our domestic environment deprived of immunohistochemical facilities, diagnosis of NID is dependent on the combined experience of the pathologist, using the HE stain, and the clinical presentation of the cases. Conclusion.- Anorectal manometry and barium enema, provide nonspecific information for NID and pathology reveals the most important diagnostic criteria.